Forest - Related Culture and Contribution to Sustainable Development in the Northern Mountain Region in Vietnam - Ngo, Thi Tan Huong; Nguyen, Thi Phuong Mai; Duong, Thi Huong; Ly, Thi Hue (Forest and Society, 2021)
The culture of communities living near/in forests indelibly interacts with forest ecosystems, both shaping and adapting to the natural environment. Forest-related cultural dimensions also provide benefits for local economies and social welfare. This study analyses the relationship between local culture and forests of the Tay and the Dao minorities and their contribution to sustainable development in Vo Nhai, a mountainous district in northern Vietnam. The study uses methods of a literature review, participant observation and qualitative interviews with local people. The strong embedded culture with forests that developed over many generations of Tay and Dao people was expressed through their knowledge systems of understanding nature, skills for environmental adaption, health protection and spiritual and recreational activities. The potentials of forest - related culture as a feature of local sustainable development were analysed through contributions in natural resource conservation, economic development and social cohesion. To integrate forest - related culture in sustainable development, some issues need to be better focused on the locality.